Classification of european building stock in technological and typological classes. (January 2022) - Landolfo, R.; Formisano, A.; Di Lorenzo, G.; Di Filippo, A.
Abstract: Nowadays it is known that the European building stock is energy-intensive and insecure: constructions need interventions both to solve performance and structural deficiencies and to reduce the current unsustainable energy waste. An intelligent retrofit for existing structures should offer an intervention integrating all the different performance requirements, such as structural safety, energy efficiency and architectural quality together with optimization of construction processes and costs. To this purpose, it is, therefore, essential to improve knowledge on the composition of the existing building stock. In this work, by analysing and processing the quantitative and qualitative data available from different countries, it has been possible to define an accurate building technologies map showing both the seismic-resistant structures and the envelope systems, the latter to evaluate also the environmental behaviour of buildings in terms of Life Cycle Assessment (LCA) and energetic consumptions. Afterwards, the seismic and climatic characteristics of all the European countries have been considered, so leading towards the definition of zones with different combined hazard conditions. Through all the possible combinations between these seismic and climatic zones, it has been conceived a hazard matrix, where different case studies can be placed aiming at showing potentialities of different retrofit solutions from seismic and energy viewpoints. The investigation of these case studies, which will be analysed in a companion paper, allows to cover all the possible constructions and hazards detected at European level, so to implement an analysis method to be used in every Countries in Europe. Highlights: Knowledge of building stock is essential for large scale seismic-energy evaluation. Smart retrofit is a structural-energetic-architectural requalification process. A hazard matrix with various seismic-climatic hazard combinations is defined. European areas with different seismic-climatic scenarios are individuated. Typical European case studies are allocated in the defined hazard matrix.